2010
DOI: 10.1359/jbmr.091025
|View full text |Cite
|
Sign up to set email alerts
|

Persistent secondary hyperparathyroidism and vertebral fractures in kidney transplantation: Role of calcium-sensing receptor polymorphisms and vitamin D deficiency

Abstract: Bone morbidity remains a major problem even after successful renal transplantation. We investigated the role of calcium-sensing receptor (CaSR) polymorphisms and 25-hydroxyvitamin D levels on the persistence of secondary hyperparathyroidism (SHPT) and their relationships with vertebral fractures (VFx) in 125 renal allograft recipients transplanted 44 AE 23 months before. All patients underwent evaluation of the main biochemical parameters of calcium metabolism as well as vertebral and femoral bone density. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 47 publications
10
38
2
2
Order By: Relevance
“…This possible relationship has been analysed in other populations. Thus, Gianini et al 18 , studied 87 women subject to renal transplant and with persistent secondary hyperparathyroidism and found negative results similar to our group. Recently, an Italian group studied risk factors for vertebral fractures in a population with primary hyperparathyroidism.…”
supporting
confidence: 87%
“…This possible relationship has been analysed in other populations. Thus, Gianini et al 18 , studied 87 women subject to renal transplant and with persistent secondary hyperparathyroidism and found negative results similar to our group. Recently, an Italian group studied risk factors for vertebral fractures in a population with primary hyperparathyroidism.…”
supporting
confidence: 87%
“…Data from our group and others suggest that the KDIGO guidelines may require revisiting and modification. In recipients managed with corticosteroids, both low 33 and high [34][35][36] PTH concentrations correlated with post-transplantation bone loss by DXA, and Giannini et al 37 found that each 1-pg/ml higher increment in PTH was associated with a significant 1% increased odds of vertebral fracture. These data suggest that optimal target levels of PTH and BTMs, based on fracture outcomes, need to be defined, that measurement of areal BMD should be obtained in kidney transplant recipients (regardless of whether they are managed with corticosteroids), and that the forearm may be the best site to assess BMD in recipients managed with ECSW.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids directly worsen bone formation by impaired genesis and increased apoptosis of osteoblasts and enhanced osteoclastogenesis through an increased RANKL/OPG ratio [30] . Both cyclosporin and tacrolimus similarly promote bone loss via direct osteoclast activation [58] , but sirolimus is administered as a bone-sparing immunosuppressive agent due to its capability to inhibit osteoclast generation [57,59] .…”
Section: Ptbd: Epidemiology and Mechanismsmentioning
confidence: 99%